Incompatibility in the administration of intravenous parenteral preparations in the intensive care unit (ICU) in one of the hospitals in Indonesia - Tobing, Johnson L.; Bangun, Hakim; Arianto, Anayanti (Institute of Computer Science (IOCS), 2025)
The prescribing and administration of intravenous injection drug therapy to patients in hospitals is increasing to achieve immediate pharmacological effects but can have a high risk of incompatibility. Therefore, it is necessary to check for intravenous injection incompatibility before administering it. Identify incompatible pairs of intravenous injectable drugs in intensive care (ICU) rooms of hospitals in Indonesia. Survey of the incompatibility of Electronic Prescribing (E-Prescribing) of intravenous injection drugs in the ICU room retrospectively using the Lexicomp application. From the results of retrospective identification of electronic prescriptions for the period from January 2022 to May 2023, data was obtained on the number of patients of 165 people, consisting of 91 people receiving compatible prescriptions and 74 patients receiving incompatible prescriptions. The number of intravenous injection drugs used was 60 types with the number of incompatible drug pairs 102 and the frequency of incompatible drugs 303. From the results of the evaluation of the incompatibility mechanism of intravenous drug injection pairs, it was found that 68 pairs of acid-base reactions, 18 pairs of mixed solvent dilution, 8 pairs of gas formation, 6 pairs of broken emulsions and 2 pairs of ionic reactions. Identification of patients' electronic prescriptions is still found to be incompatible with drug pairs, therefore it is necessary to take precautions.